Writing Style of R. K. Narayan - Sinha, Arti (Journal of Advanced Research in English & Education, 2021)
R. K. Narayan was among the first Indian English writers to be taken note of the West. With a clever use of just the right amount of humour, Narayan was able to transform his seemingly ordinary characters into larger-than-lite individuals, who brought a change in the existing social and political structures of Malgudi, a microcosmic representation of our nation. And, with this, he inspired us to think, dream and write differently to delive into a magical reality for better than the one we know. His works are often considered synonymous with the innocence of childhood, and even today the social undertones of his writing echo the complexities of the Indian society. How to cite this article:  Sinha A. Writing Style of R. K. Narayan. J Adv Res Eng & Edu 2020; 5(2): 15-17. DOI: https://doi.org/10.24321/2456.4370.202009